24. FINE-TUNING THE LAND-OCEAN CORRELATION FOR THE LATE MIDDLE PLEISTOCENE OF SOUTHERN EUROPE - Roucoux K.H.; Tzedakis P.C.; Abreu L.d.; Shackleton N.J. (My University, 2007)
A marine pollen record from the Portuguese margin provides the means of correlating vegetation changes in southern Europe with North Atlantic sea-surface temperature and the marine isotope stratigraphy for the interval 180 to 345 kyr (marine isotope stages 7, 8 and 9). It reveals close correspondence between the patterns and timing of forest expansion and contraction and changes in North Atlantic sea-surface temperatures, but pronounced offsets between marine isotopic warm stage boundaries and forested intervals. Our study confirms the previous tentative observation that the latter vary in length from one stage to another and also highlights floristic differences between sites resulting from local climatic, geological and biogeographical factors.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен